The motivational bases of public services: foundations for a third wave of research - Perry, James L. (2014)
Research on public service motivation has garnered significant attention from scholars, especially in the last two decades. This article divides the evolution of the research into three waves: definition and measurement; assessing and confirming construct validity and diffusion of the construct; and learning from past research and filling shortcomings and gaps. Significant contributions and benchmarks of the first two waves are identified. Four foundational activities are discussed that are present and will be important for advancing public service motivation research during the third wave. Some aspects of the research in the Asia Pacific region are highlighted. - Reproduced.
Keywords: Motivation